Investigating the human health implications of e-cigarettes - An in vitro mechanistic toxicology approach - SARAH MITCHELL (2022)
The number of users of e-cigarettes continues to rise, with most people opting to use electronic cigarette devices to help quit smoking tobacco cigarettes. Some non-smokers and young people are also choosing to use the devices, even if they are never-smokers. The increasing number of users of e-cigarettes and demographic of users reminds us that conducting relevant research in this area is crucial for many reasons. Although important, a lack of available relevant models to test e-cigarettes has led to a low availability of data to address concerns regarding human health hazards. Here, an in vitro model of the alveolar barrier has been created for use with a vaping machine which can directly expose cell cultures to vapour, collect emitted particles and detect chemical components independently. The model consists of an alveolar type 1-like cell line (TT1), an alveolar type 2-like cell line (NCI-H441) and macrophages (dTHP-1). This multi-cellular system formulates the ability for cells to be cultured at the air-liquid interface (ALI), that mimics the alveolar region of the human lung. Once the in vitro model was fully developed, specific e-cigarette flavour syrups were selected based on their popularity (purchase levels) and the flavours containing (the most hazardous) chemicals of interest. Flavour syrups were then exposed to cell cultures using specific puff profiles to recreate direct human exposure to understand the potential risk to human health by assessing cytotoxicity, oxidative stress, measuring (pro-)inflammatory and (pro-)fibrotic mediators, and genotoxicity. Results showed that TT1, NCI-H441 and dTHP-1 cells can be cultured together in both submerged and ALI conditions. It is proposed that this cell culture model can be successfully used in future to assess potential toxicity of e-cigarette vapours and e-liquids and be used to compare to tobacco cigarette smoke. After exposure to e-liquids and vapours, TT1 cells were most sensitive to nicotine, and overall, flavoured e-liquids and vapours caused the most pronounced effects in triple cell culture and all co-culture types. These findings suggest that e-cigarette liquids and vapours are not without risks to human health, and should be routinely assessed for toxic effects, especially when containing nicotine or flavourings.